Discrimination of Anti-Donor Response in Allogeneic Transplantation Using an Alloreactive T-Cell Detection Assay - Ryosuke Arata; Naoki Tanimine; Akhmet Seidakhmetov; Kentaro Ide; Yuka Tanaka; Hideki Ohdan (Transplant International)
Understanding donor-reactive T-cell behavior post-transplantation is challenging owing to the rarity and diversity of these cells. Here, we aimed to evaluate the relevance of an assay for rapidly detecting alloreactive T cells in a mouse transplantation model. After 18 h of one-way mixed lymphocyte reaction (MLR) culture with pre-activated donor-derived stimulators, CD4+ and CD8+ donor-reactive T cells were identified by CD154 and CD137 expression, respectively. Using full MHC mismatched mouse skin transplant models, we observed an increased donor-reactive T-cell proportion by direct presentation with elevated interferon gamma and granzyme B production 7 days post-transplantation, before graft rejection. Immunosuppression with CTLA-4 IgG and anti-CD154 antibody varied depending on donor-recipient strain combinations. On day 7, donor-reactive CD8+ T-cell proportions were lower in the tolerance model (BALB/c to C3H/HeJ) than in the rejection model (BALB/c to C57BL/6); conventional proliferation readout after 4 days of MLR could not distinguish these responses. Overall, although the conventional readout for evaluating T-cell proliferation following an MLR quantifies the precursor frequency of alloreactive T cells, the assay reported herein assesses T-cell activation markers after a short-term MLR to characterize immediate immune status. These findings offer a promising tool to elucidate immune responses post-transplantation.